Synergetic pathogenicity of Newcastle disease vaccines LaSota strain and contaminated chicken infectious anemia virus. (19th December 2018) - Su, Qi; Wang, Tuanjie; Meng, Fanfeng; Cui, Zhizhong; Chang, Shuang; Zhao, Peng
ABSTRACT: Newcastle disease virus (NDV)-attenuated vaccine has been widely used to prevent ND in poultry flocks, while many reports also mentioned the exogenous virus contamination in attenuated vaccines, which might be the reason for the widespread of some contagious diseases. Recently, the chicken infectious anemia virus (CIAV) contamination in the NDV-attenuated vaccine was also found in China, though no systemic study has studied the pathogenicity or infection mechanism of this special transmission route. Accordingly, simulation experiments were launched using CIAV isolated from a contaminated NDV-attenuated vaccine. Results showed that using NDV-attenuated vaccine contaminated with CIAV could cause CIA in chickens with obvious symptoms, including anemia, hemorrhage, lymphoatrophy, and growth retardation, while the synergistic reaction of CIAV and LaSota prompted their multiplication in vivo and disturbed the production of antibodies against each other. And CIAV could significantly reduce the NDV antibody titers and decrease the protective effectiveness. This study showed the synergetic pathogenicity of CIAV and LaSota strain after using contaminated NDV-attenuated vaccine, helping us to understand how the CIAV causes infection and induces severe diseases with a relatively low dose through the mouth, as well as reminding us that the damage of an attenuated vaccine contaminated with CIAV even in extremely low dose is not insignificant.